What Is Behind The Decline in Poverty Since 2000? Evidence from Bangladesh, Peru, and Thailand - Inchauste, Gabriela; Olivieri, Sergio; Saavedra, Jamie; Winkler, Hernan (World Bank, Washington, DC, 2013)
This paper quantifies the contributions of different factors to poverty reduction observed in Bangladesh, Peru and Thailand over the last decade. In contrast to methods that focus on aggregate summary statistics, the method adopted here generates entire counterfactual distributions to account for the contributions of demographics and income from labor and non-labor sources in explaining poverty reduction. The authors find that the most important contributor was the growth in labor income, mostly in the form of farm income in Bangladesh and Thailand and non-farm income in the case of Peru. This growth in labor incomes was driven by higher returns to individual and household endowments, pointing to increases in productivity and real wages as the driving force behind poverty declines. Lower dependency ratios also helped to reduce poverty, particularly in Bangladesh. Non-labor income contributed as well, albeit to a smaller extent, in the form of international remittances in the case of Bangladesh and through public and private transfers in Peru and Thailand. Transfers are more important in explaining the reduction in extreme compared with moderate poverty.